Polyaryletherketone composite material with high dielectric constant and low dielectric loss, preparation method and application thereof
Patent Information
- Application Number
- CN202611064023.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
AI Technical Summary
另外若采用导电填料构建渗流网络以提高介电常数,当填料含量接近渗流阈值时,复合材料会因形成导电通路而导致介电损耗明显增加,甚至丧失其绝缘性,无法满足封装材料的基本电气安全要求
[0029]本发明通过构建钙钛矿结构化合物@二氧化硅核壳结构纳米填料,以高介电钙钛矿相为核实现介电常数的大幅提升,以绝缘SiO2壳层有效阻隔界面极化与电荷迁移,显著抑制介电损耗;同时引入一维晶须与纤维无机填料,其与纳米核壳填料在尺寸上形成多尺度级配,协同构建增强网络并进一步抑制界面极化效应,从而在提升介电性能的同时保障力学强度;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyaryletherketone (PAEK) processing technology, specifically to PAEK composite materials with high dielectric constant and low dielectric loss, their preparation methods, and applications. Background Technology
[0002] Polyetheretherketone (PEEK), as a high-performance specialty engineering plastic, is considered a potential substrate material for high-end electronic packaging and circuit boards due to its excellent high-temperature resistance, chemical corrosion resistance, superior mechanical strength, and dimensional stability. An ideal substrate material not only needs extremely low dielectric loss to ensure signal integrity during transmission and reduce delay and heat generation, but also needs a suitable dielectric constant to meet the requirements of miniaturization and integration of electronic components.
[0003] The intrinsic dielectric constant of PEEK is typically only around 3.2, and its dielectric loss factor is approximately 0.004, which is insufficient to meet the high dielectric constant requirements of highly integrated devices. In existing technologies, high-dielectric ceramic fillers or conductive fillers are commonly used to improve the dielectric constant of polymers. However, the interfacial compatibility between high-dielectric ceramic fillers and the PEEK matrix is poor. This is because the PEEK molecular chains are rigid and chemically inert, making it difficult to form a strong interfacial bond with inorganic fillers, leading to voids and defects at the interface. Under high-frequency electric fields, these interfacial defects cause a sharp increase in dielectric loss, even exceeding that of the pure resin matrix. Furthermore, if conductive fillers are used to construct a percolation network to improve the dielectric constant, when the filler content approaches the percolation threshold, the composite material will form conductive pathways, leading to a significant increase in dielectric loss and even loss of insulation, failing to meet the basic electrical safety requirements of encapsulation materials. In addition, high filler content significantly increases melt viscosity, compromising the originally excellent melt processing properties of PEEK, resulting in increased brittleness and deteriorated mechanical properties in the finished product.
[0004] Therefore, the technical problem that this invention needs to solve is how to simultaneously achieve a significant increase in dielectric constant and effective suppression of dielectric loss while maintaining the excellent mechanical properties, thermal stability and good processing fluidity of PEEK. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a polyaryletherketone composite material with high dielectric constant and low dielectric loss, its preparation method, and its applications. The composite material of this invention achieves a dielectric constant of over 5 and a dielectric loss of no more than 0.005 at high frequencies while ensuring good mechanical properties.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0007] The first aspect of the present invention provides a polyaryletherketone composite material with high dielectric constant and low dielectric loss, comprising the following 100% by mass percentage materials: 20%-40% polyethersulfone-based mixed masterbatch, 8%-15% fluororesin, and the balance being polyaryletherketone.
[0008] The polyethersulfone-based mixed masterbatch comprises the following 100% by mass percentage materials: 40%-80% perovskite-structured compound@silica core-shell filler, 15%-50% one-dimensional inorganic filler, 1%-3% aminosilane coupling agent, and the balance being polyethersulfone. The high-dielectric perovskite-structured compound serves as the core to enhance the dielectric constant, while the insulating SiO2 shell suppresses losses.
[0009] Preferred polyaryletherketone composite material with high dielectric constant and low dielectric loss comprises the following 100% by mass of materials: 20%-30% polyethersulfone-based mixed masterbatch, 10% fluororesin, and the balance being polyaryletherketone.
[0010] The polyethersulfone-based mixed masterbatch comprises the following 100% by mass percentage materials: 45%-55% perovskite-structured compound@silica core-shell structured filler, 35%-45% one-dimensional inorganic filler, 1%-3% aminosilane coupling agent, and the balance being polyethersulfone.
[0011] Furthermore, the method for obtaining the perovskite-structured compound@silica core-shell structured filler is as follows: the perovskite-structured compound is dispersed in anhydrous ethanol, the system is adjusted to alkaline, and a silicon source is added dropwise under continuous stirring. After the addition is complete, the reaction is carried out at 30-60℃ for 3-8 hours. After the reaction is completed, the perovskite-structured compound@silica core-shell structured filler is obtained by solid-liquid separation, washing, and drying. No calcination is required after drying. The resulting shell is amorphous silica, which has good insulation properties. Simultaneously, the surface hydroxyl groups are retained, which is beneficial for subsequent surface modification of the silane coupling agent to improve the interfacial bonding performance with the matrix.
[0012] Furthermore, the perovskite structure compound is selected from one of strontium titanate, barium titanate, and barium strontium titanate, and the average particle size of the perovskite structure compound is 200-300 nm; the silicon source is one of tetraethyl orthosilicate and methyl orthosilicate.
[0013] The mass ratio of the perovskite-structured compound to the silicon source is 1:0.05-0.3; the mass percentage of the perovskite-structured compound in the anhydrous ethanol is 4wt%-10wt%; the pH of the system is adjusted to 9-10 using 0.1-5mol / L ammonia.
[0014] Furthermore, the one-dimensional inorganic filler is a combination of whiskers and fibers. The fibers are selected from one or more short-cut fibers selected from quartz fibers, glass fibers, alumina fibers, and boron nitride fibers. The whiskers are selected from one or more whiskers selected from silicon carbide whiskers and potassium titanate whiskers. The diameter of the fibers is 5-15 μm and the aspect ratio is 10-20. The diameter of the whiskers is 0.5-2 μm and the aspect ratio is 10-30. The fiber length, whisker length, and nano-core-shell structure filler particle size form a multi-scale gradation in size.
[0015] The aminosilane coupling agent is selected from one or more of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, bis(methyldiethoxysilylpropyl)amine, and N-(3-triethoxysilylpropyl)-4-hydroxybutyramide.
[0016] Furthermore, the polyethersulfone has a melt index of at least 10 g / 10 min at 400 °C and a load of 2.16 kg.
[0017] The polyaryletherketone is selected from one or more of polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), and polyetherketoneetherketoneketone (PEKEKK), and the polyaryletherketoneetherketoneketone (PEKEKK) has a melt index of 5-30 g / 10 min at 400°C and 2.16 kg load.
[0018] Furthermore, the fluororesin is selected from one or more of tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene alternating copolymer (ETFE), and ethylene-trifluorochloroethylene alternating copolymer (ECTFE). These fluororesins have better processability than PTFE through melt extrusion injection molding and exhibit extremely low dielectric loss.
[0019] Furthermore, the composite material must simultaneously meet at least the following conditions: dielectric constant ≥ 5.0, dielectric loss ≤ 0.005, and tensile strength ≥ 85 MPa at 10 GHz.
[0020] A second aspect of the present invention provides a method for preparing the above-mentioned polyaryletherketone composite material with high dielectric constant and low dielectric loss, comprising the following steps:
[0021] S1. Weigh the materials according to the ratio, mix the perovskite structure compound@silica core-shell structure filler and one-dimensional inorganic filler, spray in the aminosilane coupling agent, mix evenly at 80-100℃ to obtain the modified composite filler.
[0022] S2. After uniformly mixing the modified composite filler with polyethersulfone, the mixture is melt-blended, extruded, and granulated to obtain polyethersulfone-based mixed masterbatch.
[0023] S3. The polyethersulfone-based mixed masterbatch, fluororesin and polyaryletherketone are mixed evenly and then melt-blended, extruded and granulated to obtain a polyaryletherketone composite material with high dielectric constant and low dielectric loss.
[0024] Furthermore, in S1, the mixture is stirred at 80-100℃ for 15-30 minutes at a speed of 800-2000 rpm.
[0025] The parameters for each section of the melt blending extrusion in S2 are as follows: Zone 1 340-350℃, Zone 2 350-360℃, Zone 3 360-370℃, Zone 4 370-380℃, Die head 360-370℃, Screw speed 150-250rpm;
[0026] The extruder parameters for melt blending extrusion in S3 are: twin-screw extrusion, zone 1 350-360℃, zone 2 360-370℃, zone 3 370-380℃, zone 4 375-385℃, die head 365-375℃, and screw speed 150-300rpm.
[0027] The third aspect of the present invention provides the application of the above-mentioned polyaryletherketone composite material with high dielectric constant and low dielectric loss in electronic devices.
[0028] Beneficial technical effects:
[0029] This invention constructs a perovskite-structured compound@silica core-shell nanofiller, which significantly improves the dielectric constant by using a high-dielectric perovskite phase as the core and an insulating SiO2 shell to effectively block interfacial polarization and charge migration, thus significantly suppressing dielectric loss. At the same time, one-dimensional whiskers and fiber inorganic fillers are introduced, which form a multi-scale gradation with the nanocore-shell filler in terms of size, synergistically constructing a reinforcing network and further suppressing the interfacial polarization effect, thereby improving dielectric properties while ensuring mechanical strength.
[0030] A mixed masterbatch was prepared by using polyethersulfone to composite filler, which significantly improved the interfacial compatibility between the rigid polyaryletherketone matrix and the inorganic filler and reduced interfacial defects. Low dielectric loss fluoropolymer was compounded to further regulate the dielectric properties of the overall composite material by utilizing its extremely low dielectric loss characteristics.
[0031] The composite material of this invention has a dielectric constant of 5 or higher, a dielectric loss of no more than 0.005 at a high frequency of 10 GHz, and a tensile strength of at least 85 MPa. It achieves simultaneous optimization of dielectric and mechanical properties and is suitable for high-performance electronic packaging and circuit board materials. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0033] Unless otherwise specifically stated, the numerical values set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that values expressed, for example, as "within the range of ab" or "between the range of ab," do not include the endpoint values a and b; values expressed as "for ab," "is ab," or "ab" include the endpoint values a and b.
[0034] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.
[0035] Preparation Example 1
[0036] This case study describes the preparation of barium strontium titanate@silicon dioxide (BST@SiO2) core-shell structured filler, which includes the following steps:
[0037] Ten parts by weight of barium strontium titanate (BST) nanoparticles (average particle size 250 nm) were dispersed in 200 parts by weight of anhydrous ethanol. A 1 mol / L ammonia solution was added to adjust the pH value to the range of 9-10 (9.5 in this case). 1.5 parts by weight of tetraethyl orthosilicate (TEOS) were slowly added dropwise under stirring. After the addition was complete, the reaction was carried out at 50 °C for 5 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain BST@SiO2 core-shell structured filler (where BST accounted for 92 wt% of the core and SiO2 accounted for 8 wt% of the shell, with an average particle size of 260 nm).
[0038] Example 1
[0039] This case study describes the preparation of a polyaryletherketone composite material with high dielectric constant and low dielectric loss, including the following steps:
[0040] Formula 1: 200g polyethersulfone-based mixed masterbatch, 100g fluoropolymer (PFA, DuPont 951HP), 700g polyetheretherketone (Junhua PEEK5600G).
[0041] Formula 2: 100g of BST@SiO2 core-shell structure filler, 50g of short-cut quartz fiber, 36g of potassium titanate whiskers, 4g of KH550, and 10g of polyethersulfone (BASF E2010, melt index of 15g / 10min at 400℃ and 2.16KG) from Preparation Example 1;
[0042] S1. Weigh the materials according to Formula 2. After drying the filler, add the BST@SiO2 core-shell structure filler, short-cut quartz fiber (diameter 10μm, aspect ratio 15), and potassium titanate whiskers (diameter 1μm, aspect ratio 20) from Preparation Example 1 into a high-speed mixer. Turn on the mixing and stirring. Spray KH550 into the mixture. After spraying, mix at 90℃ and 1000rpm for 20min to obtain the modified composite filler.
[0043] S2. After the modified composite filler and polyethersulfone are mixed evenly, they are melt-blended and extruded and granulated. The extrusion parameters are set as follows: Zone 1 345℃, Zone 2 355℃, Zone 3 365℃, Zone 4 375℃, Die head 365℃, and screw speed 200rpm to obtain polyethersulfone-based mixed masterbatch.
[0044] S3. After uniformly mixing the polyethersulfone-based mixed masterbatch, fluororesin, and polyetheretherketone according to formula 1, the mixture is added to a twin-screw extruder for melt blending and extrusion. The extruder temperature is set as follows: Zone 1 360℃, Zone 2 365℃, Zone 3 375℃, Zone 4 380℃, and Die head 375℃. The screw speed is 200 rpm. The extruded strip is water-cooled, air-dried, and pelletized to obtain composite material particles, which are polyaryletherketone composite materials with high dielectric constant and low dielectric loss.
[0045] Example 2
[0046] This case study describes the preparation of a polyaryletherketone composite material with high dielectric constant and low dielectric loss, including the following steps:
[0047] Formula 1: 300g polyethersulfone-based mixed masterbatch, 100g fluoropolymer (PFA, DuPont 951HP), 600g polyetheretherketone (Junhua PEEK5600G).
[0048] Formula 2: 150g of BST@SiO2 core-shell structure filler, 75g of short-cut quartz fiber, 54g of potassium titanate whiskers, 6g of KH550, and 15g of polyethersulfone (BASF E2010) as in Example 1.
[0049] S1. Weigh the materials according to Formula 2. After drying the filler, add BST@SiO2 core-shell structure filler, short-cut quartz fiber (diameter 10μm, aspect ratio 15), and potassium titanate whiskers (diameter 1μm, aspect ratio 20) into a high-speed mixer. Turn on the mixing and stirring. Spray KH550 into the mixture. After spraying, mix at 90℃ and 1000rpm for 20min to obtain the modified composite filler.
[0050] S2. After the modified composite filler and polyethersulfone are mixed evenly, they are melt-blended and extruded and granulated. The extrusion parameters are set as follows: Zone 1 345℃, Zone 2 355℃, Zone 3 365℃, Zone 4 375℃, Die head 365℃, screw speed 200rpm, to obtain polyethersulfone-based mixed masterbatch.
[0051] S3. After uniformly mixing the polyethersulfone-based mixed masterbatch, fluororesin, and polyaryletherketone according to formula 1, the mixture is added to a twin-screw extruder for melt blending and extrusion. The extruder temperature is set as follows: Zone 1 360℃, Zone 2 365℃, Zone 3 375℃, Zone 4 380℃, and Die Head 375℃. The screw speed is 200 rpm. The extruded strip is water-cooled, air-dried, and pelletized to obtain composite material particles, which are polyaryletherketone composite materials with high dielectric constant and low dielectric loss.
[0052] Example 3
[0053] This case study describes the preparation of a polyaryletherketone composite material with high dielectric constant and low dielectric loss, including the following steps:
[0054] Formula 1: 400g polyethersulfone-based mixed masterbatch, 100g fluoropolymer (PFA, DuPont 951HP), 500g polyetheretherketone (Junhua PEEK5600G).
[0055] Formula 2: 200g of BST@SiO2 core-shell structure filler, 100g of short-cut quartz fiber, 72g of potassium titanate whiskers, 8g of KH550, and 20g of polyethersulfone (BASF E2010) from Preparation Example 1;
[0056] S1. Weigh the materials according to Formula 2. After drying the filler, add BST@SiO2 core-shell structure filler, short-cut quartz fiber (diameter 10μm, aspect ratio 15), and potassium titanate whiskers (diameter 1μm, aspect ratio 20) into a high-speed mixer. Turn on the mixing and stirring. Spray KH550 into the mixture. After spraying, mix at 90℃ and 1000rpm for 20min to obtain the modified composite filler.
[0057] S2. After the modified composite filler and polyethersulfone are mixed evenly, they are melt-blended and extruded and granulated. The extrusion parameters are set as follows: Zone 1 345℃, Zone 2 355℃, Zone 3 365℃, Zone 4 375℃, Die head 365℃, screw speed 200rpm, to obtain polyethersulfone-based mixed masterbatch.
[0058] S3. After uniformly mixing the polyethersulfone-based mixed masterbatch, fluororesin, and polyaryletherketone according to formula 1, the mixture is added to a twin-screw extruder for melt blending and extrusion. The extruder temperature is set as follows: Zone 1 360℃, Zone 2 365℃, Zone 3 375℃, Zone 4 380℃, and Die Head 375℃. The screw speed is 200 rpm. The extruded strip is water-cooled, air-dried, and pelletized to obtain composite material particles, which are polyaryletherketone composite materials with high dielectric constant and low dielectric loss.
[0059] Comparative Example 1
[0060] This case involves pure PEEK resin (Junhua Co., Ltd. PEEK5600G).
[0061] Comparative Example 2
[0062] The composite material in this case does not contain fluoropolymer, and the weight of materials and other preparation processes are the same as in Example 1.
[0063] Comparative Example 3
[0064] The composite material in this case does not contain BST@SiO2 core-shell structure filler, and the weight of materials and other preparation processes are the same as in Example 1.
[0065] Comparative Example 4
[0066] The composite material in this case does not contain polyethersulfone; that is, a polyethersulfone-based mixed masterbatch was not prepared in this case. Instead, the modified composite filler of S1 was directly reacted with fluoropolymer and polyetheretherketone in S3. The weight of materials and other preparation processes are the same as in Example 1.
[0067] Comparative Example 5
[0068] The composite material in this case does not contain fibers or whiskers; that is, S1 yields a modified BST@SiO2 core-shell structure filler. The weight of materials and other preparation processes are the same as in Example 1.
[0069] Comparative Example 6
[0070] In this case, the composite material was prepared by directly melt-blending and extruding with BST (not made into a core-shell filler), fibers, and whiskers modified with a silane coupling agent, and then with PEEK, PES, and fluororesin through a single process. The weight of materials and the preparation process of S1 and S3 were the same as in Example 1.
[0071] Test case
[0072] The performance of the composite materials in the above cases was tested, and the results are shown in Table 1.
[0073] Table 1. Composite material properties of examples and comparative examples
[0074]
[0075] As shown in Table 1, the dielectric constant of the material of the present invention reaches 5.1 (10 GHz) or higher, while the dielectric loss is low. This achieves the excellent effect of significantly improving the dielectric constant while reducing the dielectric loss compared to pure PEEK.
[0076] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A polyaryletherketone composite material with high dielectric constant and low dielectric loss, characterized in that, Includes the following materials in 100% by mass percentage: 20%-40% polyethersulfone-based mixed masterbatch, 8%-15% fluoropolymer, and the balance being polyaryletherketone; The polyethersulfone-based mixed masterbatch comprises the following 100% by mass percentage materials: 40%-80% perovskite-structured compound@silica core-shell structured filler, 15%-50% one-dimensional inorganic filler, 1%-3% aminosilane coupling agent, and the balance being polyethersulfone.
2. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 1, characterized in that, The method for obtaining the perovskite-structured compound@silica core-shell structured filler is as follows: the perovskite-structured compound is dispersed in anhydrous ethanol, the system is adjusted to alkaline, and a silicon source is added dropwise under continuous stirring. After the addition is complete, the reaction is carried out at 30-60℃ for 3-8 hours. After the reaction is completed, the perovskite-structured compound@silica core-shell structured filler is obtained by solid-liquid separation, washing, and drying.
3. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 2, characterized in that, The perovskite-structured compound is selected from one of strontium titanate, barium titanate, and barium strontium titanate, and the average particle size of the perovskite-structured compound is 200-300 nm; the silicon source is one of tetraethyl orthosilicate and methyl orthosilicate. The mass ratio of the perovskite-structured compound to the silicon source is 1:0.05-0.3; the mass percentage of the perovskite-structured compound in the anhydrous ethanol is 4wt%-10wt%; the pH of the system is adjusted to 9-10 using 0.1-5mol / L ammonia.
4. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 1, characterized in that, The one-dimensional inorganic filler is a combination of whiskers and fibers. The fibers are selected from one or more short-cut fibers selected from quartz fibers, glass fibers, alumina fibers, and boron nitride fibers. The whiskers are selected from one or more whiskers selected from silicon carbide whiskers and potassium titanate whiskers. The diameter of the fibers is 5-15 μm and the aspect ratio is 10-20. The diameter of the whiskers is 0.5-2 μm and the aspect ratio is 10-30. The aminosilane coupling agent is selected from one or more of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, bis(methyldiethoxysilylpropyl)amine, and N-(3-triethoxysilylpropyl)-4-hydroxybutyramide.
5. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 1, characterized in that, The polyethersulfone has a melt index of at least 10 g / 10 min at 400 °C and 2.16 KG load; The polyaryletherketone is selected from one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone, and polyetherketoneetherketoneketone, and the polyaryletherketoneetherketoneketone has a melt index of 5-30 g / 10 min at 400 °C and 2.16 KG load.
6. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 1, characterized in that, The fluororesin is selected from one or more of tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, ethylene-tetrafluoroethylene alternating copolymer, and ethylene-trifluorochloroethylene alternating copolymer.
7. The polyaryletherketone composite material with high dielectric constant and low dielectric loss according to any one of claims 1-6, characterized in that, The composite material must simultaneously meet at least the following conditions: dielectric constant ≥ 5.0, dielectric loss ≤ 0.005, and tensile strength ≥ 85 MPa at 10 GHz.
8. A method for preparing a polyaryletherketone composite material with high dielectric constant and low dielectric loss, characterized in that, The preparation of the polyaryletherketone composite material according to any one of claims 1-7 comprises the following steps: S1. Weigh the materials according to the ratio, mix the perovskite structure compound@silica core-shell structure filler and one-dimensional inorganic filler, spray in the aminosilane coupling agent, mix evenly at 80-100℃ to obtain the modified composite filler. S2. After uniformly mixing the modified composite filler with polyethersulfone, the mixture is melt-blended, extruded, and granulated to obtain polyethersulfone-based mixed masterbatch. S3. The polyethersulfone-based mixed masterbatch, fluororesin and polyaryletherketone are mixed evenly and then melt-blended, extruded and granulated to obtain a polyaryletherketone composite material with high dielectric constant and low dielectric loss.
9. The method for preparing the polyaryletherketone composite material with high dielectric constant and low dielectric loss according to claim 8, characterized in that, Mix in S1 at 80-100℃ for 15-30 minutes, with a mixing speed of 800-2000 rpm; The parameters for each section of the melt blending extrusion in S2 are as follows: Zone 1 340-350℃, Zone 2 350-360℃, Zone 3 360-370℃, Zone 4 370-380℃, Die head 360-370℃, Screw speed 150-250rpm; The extruder parameters for melt blending extrusion in S3 are: twin-screw extrusion, zone 1 350-360℃, zone 2 360-370℃, zone 3 370-380℃, zone 4 375-385℃, die head 365-375℃, and screw speed 150-300rpm.
10. The application of polyaryletherketone composite materials with high dielectric constant and low dielectric loss in electronic devices, characterized in that, The composite material is the polyaryletherketone composite material as described in any one of claims 1-7, or the polyaryletherketone composite material prepared by the preparation method as described in any one of claims 8-9.